2016
DOI: 10.1002/ejic.201501380
|View full text |Cite
|
Sign up to set email alerts
|

Mononuclear Iron‐(hydro/semi)quinonate Complexes Featuring Neutral and Charged Scorpionates: Synthetic Models of Intermediates in the Hydroquinone Dioxygenase Mechanism

Abstract: Neutral and anionic scorpionate ligands have been employed to generate active-site models of hydroquinone dioxygenases (HQDOs). While the nonheme Fe center in nearly all HQDOs is coordinated to one Asp (or Glu) and two His residues, 1,2-gentisate dioxygenase (GDO) is unique in featuring a three His triad instead. A synthetic GDO model was therefore prepared with the neutral tris(4,5-diphenyl-1-methylimidazol-2yl)phosphine ( Ph2 TIP) ligand. The gentisate substrate was mimicked with the bidentate ligand 2-(1-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 120 publications
0
8
0
Order By: Relevance
“…The increase in χ T as the temperature was raised from 50 to 300 K is likely due to the thermal population of the S = 5 / 2 excited state. Interestingly, Fiedler’s mononuclear five-coordinate iron(II) p -semiquinonate complexes exhibit ferromagnetic coupling between the high-spin iron(II) center and the p -semiquinonateradical to yield an S = 5 / 2 ground state, as indicated by electron paramagnetic resonance (EPR) and DFT data 57 , 58 . The ferromagnetic coupling observed in the iron(II) p -semi-quinonate complexes (DFT-computed J values of ~65 cm −1 , H = −2 JS 1 ∙ S 2 ) was attributed to the orthogonal orientation of the magnetic orbitals.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in χ T as the temperature was raised from 50 to 300 K is likely due to the thermal population of the S = 5 / 2 excited state. Interestingly, Fiedler’s mononuclear five-coordinate iron(II) p -semiquinonate complexes exhibit ferromagnetic coupling between the high-spin iron(II) center and the p -semiquinonateradical to yield an S = 5 / 2 ground state, as indicated by electron paramagnetic resonance (EPR) and DFT data 57 , 58 . The ferromagnetic coupling observed in the iron(II) p -semi-quinonate complexes (DFT-computed J values of ~65 cm −1 , H = −2 JS 1 ∙ S 2 ) was attributed to the orthogonal orientation of the magnetic orbitals.…”
Section: Resultsmentioning
confidence: 99%
“…145,146,147,148,149,150,151 Studies of relevant model complexes have confirmed that such an intermediate is feasible due to the "noninnocent" nature of dioxolene ligands. 152,153,154,155,156,157 However, spectroscopic studies of Fe-HPCD employing mutant enzyme and/or unactivated substrate have failed to detect a catalytically viable Fe(II)/SQ species, 158,159,160 and a recent density functional theory (DFT) analysis of the iron-based mechanism favored a superoxo-Fe(III)-catecholate description instead. 161 Thus, the precise electronic structure of the M/O2 adduct remains a matter of dispute, and we will return to this topic below.…”
Section: Extradiol Catechol Dioxygenasesmentioning
confidence: 99%
“…Fiedlersg roup has recently shown that mononuclear iron(III) 2-(1-methylbenzimidazol-2-yl)hydroquinonate complexes of tridentate facial N 3 ligands undergo deprotonation to generate the corresponding iron(II) semiquionate radical species. [26] Thes uperoxide radical (II)c an attack the C1 carbon of the carboxysemiquinonato group to form an alkylperoxide intermediate (III). [27] The para-hydroxy group on the aromatic ring then participates in directing the heterolytic O À Oc leavage of the alkylperoxo intermediate (III)t hrough Criegee type rearrangement to form an anhydride intermediate (IV).…”
mentioning
confidence: 99%